E-democracy and the parrhesia language of netizen towards COVID-19 pandemic - Arafah, Burhanuddin; Hasyim, Muhammad; Kapoyos, Fransisca E. (Linguistics and Culture Review, 2021)
The world has entered the era of digital democracy. Netizens (citizens of the internet) can deliver the facts or truths of an event through online media. On the other hand, the Coronavirus (COVID-19) pandemic has changed world order in different terms. The netizens can use parrhesia to deliver views to the world through internet. This paper studies the parrhesia democracy by netizens about COVID-19. The used questions were answered by the discourse semiotics approach. Data collection was done through distributing questionnaires online. The results revealed that the netizens’ freedom to use parrhesia concerning COVID-19 on the internet media raises ambiguous facts or information. Various myths or hoaxes that spread on social media have confused people in dealing with COVID-19. Social media with e-democracy provides free and uncontrolled opportunities in distributing opinions. However, the freedom to provide information without based on facts also results in myths or hoaxes which, later, have a universal meaning in society.